What is meaning? - Soames, Scott (Soochow University lectures in philosophy., 2010)
The tradition descending from Frege and Russell has typically treated theories of meaning either as theories of meanings (propositions expressed), or as theories of truth conditions. However, propositions of the classical sort don't exist, and truth conditions can't provide all the information required by a theory of meaning. In this book, one of the world's leading philosophers of language offers a way out of this dilemma. Traditionally conceived, propositions are denizens of a "third realm" beyond mind and matter, "grasped" by mysterious Platonic intuition. As conceived here, they are cognit.